Transforming Agricultural Land into Residential Areas: A Socio-Economic Study in Tamiang Subdistrict, Mandailing Natal Regency - Nurhayati, Nurhayati; Putra, Ilham Mirzaya (TEMALI : Jurnal Pembangunan Sosial, 2024)
The conversion of agricultural land into residential areas has become increasingly prevalent due to rapid population growth and the rising demand for housing development. This process presents various challenges, particularly for communities that rely on agriculture as their primary source of livelihood. This study aims to examine the socio-economic impacts of agricultural land conversion into residential areas in Tamiang Village, Kotanopan Subdistrict, Mandailing Natal Regency, North Sumatra Province. Using a qualitative method with data collected through observation, interviews, and literature review, the study found that land conversion in Tamiang Village has reduced the amount of agricultural land, altered land ownership patterns, and shifted livelihoods from agriculture to non-agricultural sectors. Factors such as population growth, economic motivations, inheritance considerations, and the strategic location of the land are the main drivers of this conversion. The findings of this study provide insights into the socio-economic dynamics in rural areas and offer considerations for formulating policies that balance residential development with agricultural sustainability.